Personalized outcomes for hip and knee replacement: the patients point of view - Robin R. Whitebird; Leif I. Solberg; Jeanette Y. Ziegenfuss; Stephen E. Asche; Christine K. Norton; Marc F. Swiontkowski; Steven P. Dehmer; Elizabeth S. Grossman (SpringerOpen, 2021)
Abstract Background Patient reported outcome measures (PROMs) are increasingly being incorporated into clinical and surgical care for assessing outcomes. This study examined outcomes important to patients in their decision to have hip or knee replacement surgery, their perspectives on PROMs and shared decision-making, and factors they considered important for postoperative care. Methods A cross-sectional study employing survey methods with a stratified random sample of adult orthopedic patients who were scheduled for or recently had hip or knee replacement surgery. Results In a representative sample of 226 respondents, patients identified personalized outcomes important to them that they wanted from their surgery including the ability to walk without pain/discomfort, pain relief, and returning to an active lifestyle. They preferred a personalized outcome (54%) that they identified, compared to a PROM score, for tracking progress in their care and thought it important that their surgeon know their personal outcomes (63%). Patients also wanted to engage in shared decision-making (79%) about their post-surgical care and identified personal factors important to their aftercare, such as living alone and caring for pets. Conclusions Patients identified unique personalized outcomes they desired from their care and that they wanted their orthopedic surgeons to know about. Asking patients to identify their personalized outcomes could add value for both patients and surgeons in clinical care, facilitating more robust patient involvement in shared decision-making.